RBFT: a new Byzantine fault-tolerant consensus mechanism based on Raft cluster - Dongyan HUANG; Lang LI; Bin CHEN; Bo WANG (Tongxin xuebao)
The existing consensus mechanisms of consortium blockchain are not scalable enough to provide low latency, high throughput and security while supporting large-scale network.A new consensus mechanism called RBFT was proposed to improve scalability, which was a two-level consensus mechanism with supervised nodes based on the idea of network fragmentation.In RBFT, the nodes were firstly divided into several groups.Each group adopted the improved Raft mechanism to reach consensus and select leader.Then, the leaders of each group formed the network committee, and the network committee adopted PBFT mechanism for consensus.Comparative experiments verify that RBFT can tolerant Byzantine fault while ensuring high consensus efficiency in large-scale network compared with PBFT and Raft.